46.1k views
2 votes
Which expression is equivalent to 7 sqrt x^2/5 sqrt y^3

Which expression is equivalent to 7 sqrt x^2/5 sqrt y^3-example-1
User Tauheedah
by
5.2k points

2 Answers

4 votes

Answer:

The correct option is 1

Explanation:

Given the expression


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}

we have to simplify the above


\sqrt[7]{x^2}=(x^2)^{(1)/(7)}=x^{(2)/(7)}


\sqrt[5]{y^3}=(y^3)^{(1)/(5)}=y^{(3)/(5)}

The expression becomes


\frac{\sqrt[7]{x^2}}{\sqrt[5]{y^3}}=\frac{x^{(2)/(7)}}{y^{(3)/(5)}}=[x^{(2)/(7)}][y^{(-3)/(5)}]

Hence, the correct option is 1

User Jtymann
by
4.1k points
4 votes

Answer:

Option A
x^{(2)/(7)}*y^{-(3)/(5)}

Explanation:

we have


\frac{\sqrt[7]{x^(2)}}{\sqrt[5]{y^(3)}}

we know that


\sqrt[7]{x^(2)}=x^{(2)/(7)}


\sqrt[5]{y^(3)}=y^{(3)/(5)}

substitute in the expression


\frac{x^{(2)/(7)}}{y^{(3)/(5)}}=x^{(2)/(7)}*y^{-(3)/(5)}

User Farrukh
by
5.2k points